Evaluation of the QuEChERS-LC/MS/MS method to determine residues of 31 pesticides in samples of foods with high and low moisture content - Leyva-Morales, J R; Bastidas-Bastidas, P J; Olmeda-Rubio, C; Pineda-Landeros, J M; Barraza-Lobo, A I; Romero-Bañuelos, C A; Navidad-Murrieta, M S; Zambrano-Soria, M (Revista Bio Ciencias, 2017)
The determination of residues of pesticides in foods, mainly in fresh fruits and vegetables, is of great relevance in the agro-food safety. Currently, food safety is a basic requirement of food quality, therefore progress in this area and the expansion of international trade are compatible and mutually reinforcing.